Association between self-reported food intake and subjective sleep quality among truck drivers in a city in Southern Brazil - Letícia Paviani; Edmarlon Girotto; Anne Cristine Rumiato; Renne Rodrigues; Alberto Durán González (Elsevier, 2023)
Introduction: Sleep is an activity of great importance for maintaining the homeostasis of the human body and some components may interfere with the quality of sleep, including the pattern of food consumption. Truck drivers may constitute a population particularly sensitive to this association, since they are routinely exposed to situations that may interfere with food intake and sleep quality. Thus, this study investigated the association between self-reported food intake and sleep quality in truck drivers. Methods: This was a cross-sectional study, with drivers who traveled in a city in southern Brazil. Food intake was evaluated through the average of food intake over the last 30 days. Food intake was evaluated in two forms: division in food groups and evaluation only tryptophan-rich foods. Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI). In addition to the descriptive analysis, to identify possible associations between food intake and sleep quality, linear regression, crude and adjusted for confounding variables, were performed to obtain the Beta and Beta adjusted (Betaadj), respectively, and p-value. Results: A total of 352 truck drivers, mostly males, mean age 48.4 (±11.6) years, with a frequent consumption of meat, fruits, vegetables, sweets, and energy drinks participated in this study. The frequent consumption of dairy products (Betaadj: --0.614. p-value 0.004) and fruits (Betaadj: --0.342. p-value 0.034) was associated with lower PSQI score, while the consumption of energy drinks was associated with a higher PSQI score (Betaadj: 0.923. p-value <0.001). The frequency of consumption of tryptophan-rich foods was not associated with sleep quality. Conclusion: Fruits and dairy products are associated with better subjective sleep quality, while energy drinks are associated with worse sleep quality in truck drivers, whereas dietary tryptophan-rich foods intake was not associated with sleep quality.